Beyond Anthropology, Towards Actuality - Hamilton, Annette (The Australian journal of anthropology, 2003)
Anthropology in Australia is at a critical juncture. This paper discusses the way in which the discipline has been challenged at the institutional level, in part due to pressures arising from economic rationalisation within universities. Anthropology, however, must take some responsibility for its condition. Psychology has established itself as the primary ‘human’ discipline to provide qualifications appropriate for professional employment. At a more scholarly level, anthropology's traditional zones of concern have been taken over by others, including history and cultural studies. Can we, and should we, demystify anthropology and its practices? Can we reposition anthropology with a broader vision of the human experience, and what will happen if we cannot?